Participação da via endocanabinoide no mecanismo de ação da Dipirona - Crunfli, Fernanda (2013)
Dipyrone is a non-steroidal anti-inflammatory drug (NSAID) used mainly as an analgesic and antipyretic. However, there are doubts concerning the mechanisms dipyrone uses to reduce the temperature, as COX (cyclooxygenase) inhibitors, stronger than dipyrone, haven’t had antipyretic effects so evident. There are some hypotheses that the mechanism of dipyrone can modulate other routes, including the route of endocannabinoids. Thus, the aim of this study was to evaluate the possible role of the endocannabinoid system in the effects induced by dipyrone based on the Tetrad effects of cannabinoids, these being: a state antinoceptivo, inducing cataleptic, hypolocomotion and hypothermia, from the hot plate test and catalepsy, and evaluation of locomotion and body temperature of the animals. For the experiments we used male Swiss mice (40-50g). In the first stage, the animals were divided into the following groups: Saline (10 mL/kg, i.p.) - control group, Dipyrone (10 mg/kg, 50 mg/kg, 200 mg/kg or 500 mg/kg, i.p.). In the second group: Vehicle, WIN 55.12-2 (0.1 mg/kg, 0.3 mg/kg or 3.0 mg/kg, i.p.) and in the third step, the groups were Vehicle (Saline, Tween and DMSO, 8:1:1, i.p.) + Saline, Vehicle + Dipyrone (200 or 500 mg/kg, ip), AM251 (3 or 10 mg/kg, i.p.) + Saline and AM251 + Dipyrone. In order to evaluate the mechanism of hypothermia was used TRPV1 receptor antagonist, capsazepine (10 mg/kg, i.p.) for temperature evaluation. For statistical analyzes were performed analysis of variance (ANOVA one-way or two-way), followed by post-test Newman-Keuls, or by multiple comparison test of Tukey- Kramer. Values p<0.05 were considered significant. According to the tests, dipyrone caused a decrease of locomotor activity, accompanied by an increase of latency to thermal analgesic response, and induced a cataleptic and hypothermic state, similar to the effects caused by the cannabinoid agonist, WIN 55,212-2. And cannabinoid antagonist AM251 reversed the effects caused by dipyrone, in relation to locomotor activity, the cataleptic response and thermal analgesic. As for hypothermia, the antagonists of CB1 and TRPV1 that reduction in body temperature caused by dipyrone accentuated. The results indicate an involvement of the endocannabinoid system, especially the CB1 receptor in analgesia, induction to the cataleptic effect and hypolocomotion. Already, as for hypothermia, there’s no involvement of CB1 and TRPV1, but there is a possibility of the involvement of other cannabinoid receptor, which requires specific experiments to better understand this system. The mechanism of dipyrone is complex and involves several other modulatory systems, including the endocannabinoid pathway.